Sinus histiocytosis with massive lymphadenopathy. Issue 4 (April 1992) - Stones, D K; Havenga, C
Abstract : Sinus histiocytosis with massive lymphadenopathy is a well recognised, but rare cause of lymphadenopathy in the first decade of life. Three cases presenting with nodal disease are described. The eyelids were involved in one case. The clinical, laboratory, and biopsy findings are discussed and compared with previously reported cases.